Exploring the experience of home education for young people with autism spectrum disorder: an interpretative phenomenological analysis - Spong, Rebecca (2020)
The number of young people being home educated has risen considerably, with a reported 20% increase each year across the last five years (Association of Directors of Children’s Services, 2019). In particular, there has been an increase in young people with Special Educational Needs (SEN) becoming home educated (Hopwood et al., 2007; Jeffreys, 2017). Several studies focusing on home education for young people with SEN found that a high number of participants had Autism Spectrum Disorder (ASD) (Kendall & Taylor, 2016; Parsons & Lewis, 2010). Despite this, research exploring the views of young people with ASD about their home education experience is scarce, particularly research that solely gathers the views of the young person.